Foreign Direct Investment Policy as an Accelerator in The Capital City of Nusantara: Comparative Study of Latin American and Caribbean - Saima Arifiah; Daffa Ladro Kusworo (Universitas Muhammadiyah Malang, 2026)
The parameters for legal certainty regarding foreign direct investment are the primary topic of this research, which will be discussed further in this article. What differentiates this research from previous studies is how to identify critical gaps regarding the lack of clear parameters for measuring legal certainty in various national projects involving foreign investors. Therefore, this research formulates the main question: how to ensure legal certainty regarding suspected foreign direct investment in the new capital city (IKN) so that systematic measurement and evaluation can be conducted. In this case, the research uses a normative juridical method, accompanied by a comparative study, examining how norms related to foreign direct investment in Indonesia compare with international regulatory standards, examining indicators such as transparency, regulatory stability, and the mechanisms used to resolve institutional disputes. The comparative analysis is drawn from countries that have successfully implemented FDI policies, particularly for large-scale infrastructure development. The results of the study show that although formally Indonesia has ratified a policy that aims to provide legal certainty, there are discrepancies in its implementation due to obstacles related to the threat of the recent economic recession, as well as the continued number of customary land disputes which have given rise to doubts about foreign investment in providing direct capital.